Students' Knowledge Regarding Basic Immunization For Infants - Angel Graceta Sitepu; Dwi Noerjoedianto; M. Ridwan; Budi Aswin; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
This study examines students' knowledge of basic immunization for infants, a crucial issue given the high infant and toddler mortality rate due to vaccine-preventable diseases. The research method used was quantitative with a cross-sectional approach. The sample size of this study was 42 students who met the inclusion criteria, with the majority of respondents being female (90.5%), 19 years old (59.5%), and in their fourth semester (85.7%). The results showed that the majority of respondents (95.2%) had received information about basic immunization for infants, with the main sources of information coming from college/academics (26.2%) and family/friends (23.8%). The level of knowledge of respondents regarding basic immunization for infants was mostly in the good category (71.4%), although a small number had insufficient knowledge (28.6%). This good level of knowledge is important for increasing awareness and coverage of immunization. Therefore, it is important to continue educating students so that they can contribute to efforts to improve public health, especially regarding infant immunization